A trip to Cusco: Three reports by Fannie B. Ward for the United States press (1891) - Arrizabalaga, Carlos (2012)
This article presents the first translations from English to Spanish of three reports about Cuzco and its monuments written in 1891 for several newspapers in the USA by the special correspondent, Fannie B. Ward. Included with the translations are clarifying notes as well as a summary of the authors ́s life along with explanation of the subjects of the reports in their historic context.